Regulating Employment Precarity in Ontario Home Care - Bartkiw, Timothy J. (Labour / Le Travail, 2020)
In the mid-1990s, the province of Ontario instituted a new model of “managed competition” to govern a significant portion of home care services delivery. The new model, based on competitive bidding for the delivery of home care services, deepened reliance on private and increasingly for-profit “service provider organizations.” In time, the outcomes of the transition to managed competition – particularly increased employment precarity and turnover – grew increasingly salient and became captured in prior literature. However, a series of subsequent responses to these outcomes also began to emerge, ostensibly aimed at improving work and employment conditions in this sector. This article provides a historical analysis of various responses to the heightened employment precarity wrought by the managed competition regime in Ontario home care, with a focus on personal support workers (psws) insofar as they have historically tended to experience the most precarious conditions among the primary home care occupations. The analysis suggests that the core institutional arrangement of fissured work and organizational relations, coupled with a hyperdecentralized bargaining structure, was a key constraint and mediating factor. The most dramatic policy measure aimed at employment precarity, the 2014 psw Wage Enhancement Initiative, constituted a major, ad hoc overriding of this structure that had until then delivered wage restraint so successfully that it challenged the government’s own health human resources objectives. This reliance on such an extraordinary ad hoc instrument, without addressing the core institutional structure, severely restricts the degree of improvement in psw employment outcomes capable of being produced by collective bargaining in Ontario home care.